Entrance to the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance gate to the Mahakal Temple, presently enclosed inside a boundary wall and thickly surrounded with flora, is now navigated through a metal gate followed by stairs leading to the surviving temple structures. It is likely that this gate once served as the main entrance, given its alignment with the garbhagriha.